The large cytoplasmic volume of oocyte - Hirohisa KYOGOKU; Tomoya S KITAJIMA (The Society for Reproduction and Development, 2022)
The study of the size of cells and organelles has a long history, dating back to the 1600s when cells were defined. In particular, various methods have elucidated the size of the nucleus and the mitotic spindle in several species. However, little research has been conducted on oocyte size and organelles in mammals, and many questions remain to be answered. The appropriate size is essential to cell function properly. Oocytes have a very large cytoplasm, which is more than 100 times larger than that of general somatic cells in mammals. In this review, we discuss how oocytes acquire an enormous cytoplasmic size and the adverse effects of a large cytoplasmic size on cellular functions.